Nano carbonyl sulfide hydrolysis catalyst carrier, catalyst and preparation method

By using nano-carbonylsulfur hydrolysis catalyst support in blast furnace gas, the problems of low efficiency and short life of existing catalysts are solved by increasing the specific surface area and pore volume, and more efficient catalytic reactions and longer service life are achieved.

CN119819280AInactive Publication Date: 2025-04-15BEIJING LUNENG QINGXIN ENVIRONMENTAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411750947.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The catalytic efficiency of COS hydrolysis catalyst in existing blast furnace gas is low and has a short service life.

Method used

By using zirconia beads as ball milling medium for nano-blasting ball milling, and by calcining-mixed granulation-drying-recalcining, a catalyst support with higher specific surface area and pore volume is prepared, increasing the catalyst reaction area and ability to support active ingredients.

Benefits of technology

The catalytic reaction rate and catalyst service life are significantly improved, the catalyst reaction area is increased by 15%-30%, and the catalyst service life is extended by 13%-30%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819280A_ABST
    Figure CN119819280A_ABST
Patent Text Reader

Abstract

The invention discloses a nanocrystallized carbonyl sulfide hydrolysis catalyst carrier, a catalyst and a preparation method, the catalyst carrier comprises the following components in parts by weight: 75-85 parts of gamma-Al2O3 powder, 2-5 parts of carboxymethyl cellulose, 2-8 parts of polyvinyl alcohol, 2-10 parts of ammonium bicarbonate and 2-10 parts of citric acid, zirconium oxide beads are adopted as a ball milling medium, and the nanocrystallized carbonyl sulfide hydrolysis catalyst carrier is prepared by ball milling. The preparation method comprises the following steps: carrying out ball milling, separation, drying, calcination, granulation, re-drying and other processes to prepare a nanocrystallization blank catalyst carrier, and carrying out loading of an active substance potassium carbonate on the nanocrystallization blank catalyst carrier in a solution soaking manner to prepare the nanocrystallization carbonyl sulfide hydrolysis catalyst. The preparation method is scientific and reasonable in technological process, and the obtained catalytic carrier and catalyst are long in service life, good in effect, suitable for industrial and large-batch production and high in application and popularization value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrolysis catalysts, is used for blast furnace gas purification, and particularly relates to a nano carbonyl sulfide hydrolysis catalyst carrier, a catalyst and a preparation method. Background Art

[0002] Blast furnace gas is a by-product combustible gas in the blast furnace ironmaking process in the steel industry and is one of the main pollutants in the steel industry. The sulfides it contains can be converted into SO2, SO3, etc. through combustion, and will form acid rain when discharged into the atmosphere, causing environmental pollution. The sulfur in blast furnace gas mainly exists in the form of carbonyl sulfide (COS). COS is also widely present in the production processes of coking, petrochemical, and chemical industries. If it is discharged into the atmosphere without treatment, it will react with oxygen to form sulfur dioxide, promote photochemical reactions and pollute the environment. Hydrolysis is the most practical method to remove COS. Through this process, it can be converted into easy-to-handle hydrogen sulfide or sulfur, which is conducive to conversion and recovery. At present, the COS hydrolysis catalyst in blast furnace gas is generally divided into two parts: a carrier and an active component. The carrier is generally γ-Al2O3, and the active component is usually an alkali metal or alkaline earth element. The catalyst carrier generally needs to have a relatively large specific surface area to have sufficient reaction area and high catalytic efficiency. Therefore, increasing the specific surface area of ​​the carrier is a reliable way to effectively improve the catalytic efficiency of the catalyst.

[0003] The invention patent with publication number CN113332969 A discloses a method for preparing a catalyst that can improve the anti-deactivation performance in the carbonyl sulfide hydrolysis reaction. By introducing a pore-forming agent and a pore-expanding agent, the mesoporous pore size of alumina can be enlarged to obtain an ordered mesoporous alumina with an enlarged mesoporous pore size. The prepared catalyst material has good catalytic ability and anti-deactivation performance for the carbonyl sulfide hydrolysis reaction. However, the specific surface area of ​​the alumina obtained by this method is not significantly improved, and the specific surface area is the most important parameter that determines the catalyst reaction area and efficiency. The invention patent with publication number CN106861655B discloses an alumina carbonyl sulfide hydrolysis catalyst and a preparation method thereof, using polystyrene microspheres as a macroporous template, P123 as a mesoporous template agent, a soluble aluminum salt as a catalyst carrier precursor, and a potassium oxalate coordination solution as an active component precursor. By using size-controllable organic microspheres as macroporous templates and regulating mesopores through mesoporous template agents, the catalyst becomes a γ-Al2O3-based COS hydrolysis catalyst with a stepped pore structure of macropores, mesopores and micropores, and the catalyst has abundant micropores to provide a reaction surface. Although this method improves the empty volume to a certain extent, the specific surface area that determines the reaction area is still not high. CN 116020434 B discloses a non-sulfur-accumulating and anti-deactivation carbonyl sulfide hydrolysis catalyst. The catalyst uses polystyrene microspheres as a hard template and a triblock copolymer as a soft template. The solvent volatilization-induced self-assembly assisted hydrothermal synthesis method is used to prepare a catalyst Mg Al2O4 with a high specific surface area and a three-dimensional ordered macroporous-mesoporous structure, but its specific surface area and other information are not disclosed. Summary of the invention

[0004] In view of the problems of low catalytic efficiency and short service life of the current COS hydrolysis catalyst, the present invention proposes a nano-sized carbonyl sulfide hydrolysis catalyst, a preparation method and a catalyst carrier, which greatly increases the area of ​​the catalyst contacting COS, thereby improving the catalytic reaction efficiency, and reduces the deposition of S and sulfate by increasing the empty volume and pore size, thereby extending the catalyst life.

[0005] The present invention is achieved in that:

[0006] In one aspect, the present invention provides a nano-sized carbonyl sulfide hydrolysis catalyst carrier, characterized in that it is composed of the following weight parts: 75-85 parts of γ-Al2O3 powder, 2-5 parts of carboxymethyl cellulose, 2-8 parts of polyvinyl alcohol, 2-10 parts of ammonium bicarbonate, 2-10 parts of citric acid, and a specific surface area of ​​280-320 m 2 / g, pore volume 0.38-0.43cm 3 / g, pore size 9.0-9.3nm, particle size 300-950nm.

[0007] The second aspect of the present invention is a nano-carbonyl sulfide hydrolysis catalyst, which is based on the above-mentioned nano-carbonyl sulfide hydrolysis catalyst carrier and is composed in weight parts: 75-85 parts of γ-Al2O3 powder, 2-5 parts of carboxymethyl cellulose, 2-8 parts of polyvinyl alcohol, 2-10 parts of ammonium bicarbonate, 2-10 parts of citric acid, and 2-12 parts of potassium carbonate.

[0008] The third aspect of the present invention is a method for preparing a nano-sized carbonyl sulfide hydrolysis catalyst. Based on the above-mentioned nano-sized carbonyl sulfide hydrolysis catalyst, the method comprises the following steps:

[0009] S1, ball milling, separation, and drying: commercially available γ-Al2O3 is nano-sized by ball milling, using zirconium oxide beads as the grinding medium. After the ball milling is completed, the zirconium oxide beads are separated and the sample is centrifuged, the supernatant is discarded, the precipitate is collected, and the precipitate is placed in an oven for drying;

[0010] S2, primary calcination: calcining the sample prepared in step S1 at high temperature to remove organic matter and crystal water to obtain high-purity nano γ-Al2O3 powder;

[0011] S3, mixing, granulating, and drying: mixing the γ-Al2O3 powder after the primary calcination with carboxymethyl cellulose, polyvinyl alcohol, ammonium bicarbonate, and citric acid in a certain proportion, granulating the mixture with a disc granulator, and drying the obtained particles;

[0012] S4, secondary calcination: drying the granules obtained in step S3 and then calcining them again to remove the pore-enlarging agent and leave the mesopores to further increase the specific surface area, thereby obtaining a nano-sized mesoporous blank catalyst carrier;

[0013] S5, loading active substances: loading the nano-sized mesoporous blank catalyst carrier prepared in S4 with active substance potassium carbonate by immersing it in a solution, and then drying it to obtain a nano-sized catalyst for use.

[0014] Furthermore, in step S1, the grinding medium uses 0.1-0.3 mm zirconia beads, the mass ratio of zirconia beads to material is 5:1-7:1, the ball milling speed is 200-700 r / min, the ball milling time is set to 1-6 h, the sample centrifugal speed is 1000-5000 rpm, the centrifugal time is 3-15 min, the drying temperature is 50-100 ° C, and the drying time is 6-48 h.

[0015] Furthermore, the high temperature calcination in step S2 is performed at a temperature of 400-650° C., a calcination time of 2-6 hours, and a heating rate of 1-8° C. / min.

[0016] Furthermore, in step S3, the γ-Al2O3 powder calcined from S2 is mixed and granulated with carboxymethyl cellulose, polyvinyl alcohol, ammonium bicarbonate and citric acid in the following weight proportions: 75-85 parts, carboxymethyl cellulose 2-5 parts, polyvinyl alcohol 2-8 parts, ammonium bicarbonate 2-10 parts, and citric acid 2-10 parts.

[0017] Furthermore, the granulation in step S3 is carried out at a granulation speed of 30-80 rpm, a granulation drying temperature of 50-100° C., and a drying time of 6-48 h.

[0018] Furthermore, the secondary calcination in step S4 is carried out at a temperature of 400-650° C., a calcination time of 2-6 hours, and a heating rate of 1-8° C. / min.

[0019] Furthermore, the solution loaded with active substances in step S5 is a potassium carbonate solution, and the solution loaded with active substances in step S5 is a potassium carbonate solution, wherein the potassium carbonate solution is 2-12 parts of potassium carbonate and 82-98 parts of water by weight, and the soaking time is 2-48 hours. After that, the catalyst pellets loaded with active substances are dried at a drying temperature of 50-100° C. and a drying time of 6-48 hours.

[0020] Furthermore, the average particle size of the γ-Al2O3 powder processed in steps S1 and S2 is 904 nm.

[0021] The beneficial effects of the present invention are:

[0022] (1) Zirconia beads are used as ball milling media for nano-ball milling, and the specific surface area and pore volume of the carrier are greatly increased through the method of calcination-mixing granulation-drying-recalcination, which increases the effective area of ​​the carrier to load the active ingredients, increases the catalyst reaction area by 15%-30%, and improves the catalytic reaction rate.

[0023] (2) By increasing the specific surface area and pore volume of the carrier, more active ingredients can be loaded, thus extending the service life of the catalyst. In addition, the increased pore volume is conducive to the release of reaction products such as hydrogen sulfide and sulfur, keeping the pores unobstructed, thereby further extending the service life of the catalyst by 13%-30%.

[0024] (3) The preparation method of the present invention has a scientific and reasonable process flow, and the obtained catalytic carrier and catalyst have a long life and good effect, are suitable for industrialization and mass production, and have strong application and promotion value.

[0025] The present invention is further explained below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a process flow chart of the preparation method of the present invention;

[0027] Figure 2 This is a Malvern particle size test diagram of the γ-Al2O3 carrier of Examples 4-6 of the present invention;

[0028] Figure 3 It is a graph showing the catalytic performance test results of Examples 4-6 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0029] Embodiment 1:

[0030] This embodiment is a nano-carbonyl sulfide hydrolysis catalyst carrier, which is composed of the following parts by weight: 75-85 parts of γ-Al2O3 powder, 2-5 parts of carboxymethyl cellulose, 2-8 parts of polyvinyl alcohol, 2-10 parts of ammonium bicarbonate, and 2-10 parts of citric acid. The specific surface area of ​​the catalyst carrier is 280-320m 2 / g, pore volume 0.38-0.43cm 3 / g, pore size 9.0-9.3nm, particle size 300-950nm.

[0031] Embodiment 2:

[0032] Based on Example 1, this example is a nano-carbonyl sulfide hydrolysis catalyst, which is composed by weight: 75-85 parts of γ-Al2O3 powder, 2-5 parts of carboxymethyl cellulose, 2-8 parts of polyvinyl alcohol, 2-10 parts of ammonium bicarbonate, 2-10 parts of citric acid, and 2-12 parts of potassium carbonate.

[0033] Embodiment 3:

[0034] This embodiment is a nano carbonyl sulfide hydrolysis catalyst and a preparation method, based on the catalyst carrier and catalyst described in the above embodiment, such as Figure 1-3 As shown, the preparation method steps are as follows:

[0035] S1, ball milling, separation, and drying: The commercially available γ-Al2O3 is nano-sized by ball milling. Zirconia beads are used as the grinding medium and water is added for ball milling. After the zirconia beads are ball milled, the zirconia beads are separated, the sample is centrifuged, the supernatant is discarded, the precipitate is collected, and the precipitate is placed in an oven for drying.

[0036] The ball mill uses zirconia beads with a diameter of 0.1-0.3 mm as the grinding medium, and water is added for ball milling. The weight ratio of zirconia beads, materials and water is 5:1:4. The ball mill speed is 200-700 r / min, the ball mill time is set to 1-6 h, the centrifugal speed is 1000-5000 rpm, the centrifugal time is 3-15 min, the drying temperature is 50-100 ° C, and the drying time is 6-48 h.

[0037] S2, primary calcination: calcine the sample prepared in step S1 at high temperature to remove organic matter and crystal water, and obtain high-purity nano γ-Al2O3 powder. The high-temperature calcination temperature is 400-650°C, the calcination time is 2-6h, and the heating rate is 1-8°C / min. The average particle size of the nano γ-Al2O3 powder obtained after processing is 904nm.

[0038] Figure 2 This is a Malvern particle size test diagram of the γ-Al2O3 carrier prepared by the preparation method of the present invention, which shows the particle size distribution of the γ-Al2O3 carrier prepared by the method of the present invention and the strength of different particle sizes. The statistical results of the particle size test of the γ-Al2O3 carrier Malvern particle size tester are shown in Table 4 below:

[0039] Table 1 Statistical table of particle size detection of γ-Al2O3 carrier Malvern particle size analyzer

[0040] name average value Z average value (nm) 904.1 Peak area by intensity (%) 100 Peak-intensity average value (nm) 429.1 Peak width (nm) 39.43 Average count rate (kops) 416.8

[0041] S3, mixing, granulating, and drying: the γ-Al2O3 powder calcined in step S2 is mixed with carboxymethyl cellulose, polyvinyl alcohol, ammonium bicarbonate, and citric acid in a certain proportion, granulated by a disc granulator, and the obtained particles are dried.

[0042] Preferably, γ-Al2O3 powder is mixed with carboxymethyl cellulose, polyvinyl alcohol, ammonium bicarbonate and citric acid in the following weight proportions: 75-85 parts, 2-5 parts of carboxymethyl cellulose, 2-8 parts of polyvinyl alcohol, 2-10 parts of ammonium bicarbonate and 2-10 parts of citric acid. The granulation speed is 30-80rpm, the granule drying temperature is 50-100°C and the drying time is 6-48h.

[0043] S4, secondary calcination: After drying the granules from step S3, calcining is performed again, mainly to remove the pore-enlarging agent and leave the mesopores to further increase the specific surface area. The calcination fully burns the granulated polymer and other components, and the product overflows in the form of gas, leaving gaps to form a large specific surface area. The calcination temperature is 400-650°C, the calcination time is 2-6h, and the heating rate is 1-8°C / min to obtain a nano-sized blank catalyst carrier.

[0044] S5, loading active substances: the prepared nanosized blank catalyst carrier is loaded with active substance potassium carbonate by solution immersion at room temperature of about 25°C, and then dried to obtain a nanosized catalyst. The solution loaded with active substances is a potassium carbonate solution, which is 2-12 parts of potassium carbonate and 82-98 parts of water by weight, and the immersion time is 2-48h, and then the catalyst pellets loaded with active substances are dried at a drying temperature of 50-100°C and a drying time of 6-48h.

[0045] The loading rate of active substances can generally reach a relatively high rate within 2 hours. The loading amount will increase with the extension of immersion time, but the loading speed will be greatly slowed down. The load is basically saturated after 48 hours, and the loading amount can basically no longer be increased after that.

[0046] Embodiment 4:

[0047] This embodiment is an improvement and refinement of Embodiments 1-3. Figure 1-3 As shown, the steps of the preparation method of the nano carbonyl sulfide hydrolysis catalyst described in this embodiment are:

[0048] S1: The commercially available γ-Al2O3 was nano-sized by ball milling, using a 500ml ball milling jar, 0.3mm zirconium oxide beads as the grinding medium, the weight ratio of zirconium oxide beads, materials and water was 5:1:6, the ball milling speed was 600r / min, and the ball milling time was set to 2h. After the ball milling was completed, the zirconium oxide beads were separated and the sample was centrifuged at 3000rpm for 10min, then the supernatant was discarded, the precipitate was collected, and the precipitate was placed in an oven for drying at a drying temperature of 85°C and a drying time of 24h.

[0049] S2: The sample prepared in S1 was calcined at a high temperature of 450°C, for 3 h, and at a heating rate of 5°C / min.

[0050] S3: The γ-Al2O3 powder calcined from S2 was mixed with carboxymethyl cellulose, polyvinyl alcohol, ammonium bicarbonate, and citric acid in a certain weight ratio, specifically, the weight ratio is: 84 parts of γ-Al2O3 powder, 4 parts of carboxymethyl cellulose, 4 parts of polyvinyl alcohol, 4 parts of ammonium bicarbonate, and 4 parts of citric acid. The sample particles were granulated by a disc granulator and dried at a drying temperature of 85°C for 24 hours.

[0051] S4: calcining again, the calcination temperature is 450°C, the calcination time is 3h, and the heating rate is 5°C / min, to obtain a nanosized blank catalyst carrier.

[0052] S5: The nano-sized carrier prepared in S4 is loaded with active substances by soaking in a solution. The potassium carbonate solution loaded with active substances is calculated by weight, with 10 parts of potassium carbonate and 90 parts of water. The soaking time is 24 hours. The carrier is then dried at 85° C. for 24 hours to obtain the catalyst for standby use.

[0053] Embodiment 5:

[0054] This embodiment is a second improvement and refinement example of the improvement and refinement of Embodiments 1-3. Figure 1-3 As shown, the steps of the preparation method of the nano carbonyl sulfide hydrolysis catalyst described in this embodiment are:

[0055] S1: The commercially available γ-Al2O3 was nano-sized by ball milling, using a 500ml ball milling jar, a 0.2mm diameter zirconia bead as the grinding medium, and water was added for ball milling. The weight ratio of zirconia bead, material and water was 6:1:7, the speed was 600r / min, and the ball milling time was set to 2h. After the ball milling was completed, the zirconia beads were separated and the sample was centrifuged at 3000rpm for 10min, then the supernatant was discarded, the precipitate was collected, and the precipitate was placed in an oven for drying at 85℃ for 24h.

[0056] S2: The sample prepared in S1 was calcined at a high temperature of 450°C, for 3 h, and at a heating rate of 5°C / min.

[0057] S3: The γ-Al2O3 powder calcined from S2 was mixed with carboxymethyl cellulose, polyvinyl alcohol, ammonium bicarbonate, and citric acid in a certain weight ratio, specifically, the weight ratio is: 84 parts of γ-Al2O3 powder, 4 parts of carboxymethyl cellulose, 4 parts of polyvinyl alcohol, 4 parts of ammonium bicarbonate, and 4 parts of citric acid. The sample particles were granulated by a disc granulator and dried at a drying temperature of 85°C for 24 hours.

[0058] S4: calcining again, the calcination temperature is 450° C., the calcination time is 3 h, and the heating rate is 5° C. / min, to obtain the nano-sized carbonyl sulfide hydrolysis catalyst carrier of the present invention.

[0059] S5: The nano-sized carbonyl sulfide hydrolysis catalyst carrier prepared in S4 is loaded with active substances by immersing in a solution. The loading conditions are the same as those in Example 5: the potassium carbonate solution loaded with active substances is calculated by weight, 10 parts of potassium carbonate and 90 parts of water, and the immersion time is 24 hours, and then it is dried at a drying temperature of 85° C. and a drying time of 24 hours to obtain the nano-sized carbonyl sulfide hydrolysis catalyst.

[0060] Embodiment 6:

[0061] Improvements and refinements of Embodiments 1-3 A third improvement and refinement example is as follows: Figure 1-3 As shown, the steps of the preparation method of the nano carbonyl sulfide hydrolysis catalyst described in this embodiment are:

[0062] S1: The commercially available γ-Al2O3 was nano-sized by ball milling, using a 500ml ball mill jar, 0.1mm zirconium oxide beads as the grinding medium, the weight ratio of zirconium oxide beads, materials and water was 7:1:9, the ball mill speed was 600r / min, and the ball milling time was set to 2h. After the ball milling was completed, the zirconium oxide beads were separated and the sample was centrifuged at 3000rpm for 10min, then the supernatant was discarded, the precipitate was collected, and the precipitate was placed in an oven for drying at a drying temperature of 85°C and a drying time of 24h.

[0063] S2: The sample prepared in S1 was calcined at a high temperature of 450°C, for 3 h, and at a heating rate of 5°C / min.

[0064] S3: The γ-Al2O3 powder calcined from S2 was mixed with carboxymethyl cellulose, polyvinyl alcohol, ammonium bicarbonate, and citric acid in a certain weight ratio, specifically, 84 parts of γ-Al2O3 powder, 4 parts of carboxymethyl cellulose, 4 parts of polyvinyl alcohol, 4 parts of ammonium bicarbonate, and 4 parts of citric acid. The sample particles were granulated by a disc granulator and dried at a drying temperature of 85°C for 24 hours.

[0065] S4: calcining again, the calcination temperature is 450°C, the calcination time is 3h, and the heating rate is 5°C / min, to obtain a nanosized blank catalyst carrier.

[0066] S5: The blank nano-sized carrier prepared in S4 is loaded with active substances by soaking in a solution, and the loading conditions are the same as those in Example 5: the potassium carbonate solution loaded with active substances is calculated by weight, 10 parts of potassium carbonate and 90 parts of water, and the soaking time is 24 hours, and then it is dried at a drying temperature of 85°C and a drying time of 24 hours to obtain the nano-sized carbonyl sulfide hydrolysis catalyst.

[0067] Comparative Example 1:

[0068] The preparation method of this comparative example is as follows:

[0069] S1: Mix the commercially available γ-Al2O3 powder with carboxymethyl cellulose, polyvinyl alcohol, ammonium bicarbonate and citric acid in a certain weight ratio, specifically: 84 parts of γ-Al2O3 powder, 4 parts of carboxymethyl cellulose, 4 parts of polyvinyl alcohol, 4 parts of ammonium bicarbonate and 4 parts of citric acid. Granulate the sample particles with a disc granulator, dry the sample particles at a temperature of 85°C and a drying time of 24h. Calcinate again at a temperature of 450°C, a calcination time of 3h and a heating rate of 5°C / min to obtain a blank catalyst carrier.

[0070] S2: The nano-sized carrier prepared in S3 is loaded with active substances by immersing it in a solution. The loading conditions are the same as those in Example 5: the potassium carbonate solution for loading the active substances is calculated by weight, comprising 10 parts of potassium carbonate and 90 parts of water. The immersion time is 24 hours. The carrier is then dried at 85°C for 24 hours to obtain the catalyst prepared by the method of Comparative Example 1, which is ready for use.

[0071] The performance of the four catalysts prepared by the methods of Examples 4-6 and Comparative Example 1 was tested. The test methods and results are as follows:

[0072] 1. Catalytic performance testing

[0073] Test equipment: 1 skid-mounted pilot device for fine desulfurization of blast furnace gas; 1 gas chromatograph; several gas sampling bags. This device is equipped with 4 hydrolysis catalytic reactors, namely reactors A, B, C, and D. Gas flow of the test device: blast furnace gas is connected to the skid-mounted pilot device from the gas main line after the blast furnace dust collector, and enters hydrolysis reactor A, hydrolysis reactor B, hydrolysis reactor C, and hydrolysis reactor D respectively, and returns to the blast furnace gas main pipeline after hydrolysis catalysis.

[0074] 2. Experimental process

[0075] (1) The hydrolysis reactors A, B, C and D were respectively filled with the same volumes of porcelain balls, protective agents and the same volumes of the four catalysts prepared in Examples 1-3 and Comparative Example 1;

[0076] (2) Open the blast furnace gas pipeline valve, adjust the inlet valve and electric heater, control the gas flow and temperature entering each reactor to be basically the same, and the space velocity of the hydrolysis catalyst is 8000h -1 ;

[0077] (3) After the thermometer and pressure readings at the gas pipeline inlet are stable, start sampling at the blast furnace gas main inlet and the outlets of hydrolysis reactors A, B, C and D using sampling bags. Take a gas sample once every 4 hours for inspection and use a gas chromatograph to detect COS concentration and H2S concentration. The conditions are shown in Table 2:

[0078] Table 2 Test items and test parameter conditions

[0079] project parameter Reactor temperature measured ℃ 110 Reactor pressure MPa 0.2 <![CDATA[Gas flow rate setting Nm 3 / h]]> 24 Ceramic ball filling volume L 6 Protective agent loading amount L 3 Hydrolyzing agent loading amount L 3 <![CDATA[Calculate the airspeed h -1 > 8000

[0080] 3. Test results

[0081] The specific surface areas of Examples 4-6 and Comparative Example 1 were tested using an Anton Paar series specific surface area-pore size analyzer. The test results are shown in Table 3. Figure 2 As shown:

[0082] Table 3 Specific surface area of ​​catalyst carriers obtained by the preparation methods of Examples 4-6 and Comparative Example 1

[0083] sample <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Pore ​​size (nm) Example 4 290.7 0.39 9.01 Example 5 303.4 0.40 9.21 Example 6 310.2 0.42 9.26 Comparative Example 1 240.1 0.31 8.85

[0084] As can be seen from Table 3, the nano-sized catalyst carrier prepared by the method of the present invention, using zirconium oxide beads as ball milling media for nano-milling, and by the method of calcination-mixing granulation-drying-re-calcination, has a specific surface area increased by 21.07%-29.20% and a pore volume increased by 20.51%-35.48% compared with the control, and Example 6 is the best. This shows that the nano-sized catalyst carrier prepared by the method of the present invention can load more active ingredients, the catalytic efficiency is significantly improved, and the increased pore volume is conducive to the release of reaction products such as hydrogen sulfide and sulfur, keeping the pores unobstructed, thereby further extending the service life of the catalyst.

[0085] The catalytic performance test results of Examples 4-6 and Comparative Example 1 are shown in Tables 4 and Figure 3 As shown:

[0086] Table 4 Catalytic performance test of catalysts prepared in Examples 4-6 and Comparative Example 1

[0087]

[0088] From Table 4, Figure 3 It can be seen that the catalytic efficiency of the nano-sized catalyst of the present invention is significantly improved and the service life is greatly extended compared with the comparative example 1.

[0089] Finally, it should be noted that the embodiments described in the present invention are only preferred embodiments of the present invention, rather than limiting the embodiments of the present invention, because it is not necessary and impossible to list all the embodiments one by one. Therefore, for those skilled in the art, any form of modification or change can be made to the embodiments described in the present invention, and any form of modification, improvement or equivalent replacement made within the spirit and principle of the present invention is included in the protection scope required by the rights of the present invention.

Claims

1. A nano-carbonyl sulfide hydrolysis catalyst carrier, characterized in that: The composition is as follows: γ-Al2O3 powder 75-85 parts, carboxymethyl cellulose 2-5 parts, polyvinyl alcohol 2-8 parts, ammonium bicarbonate 2-10 parts, citric acid 2-10 parts, specific surface area 280-320 m² / g, pore volume 0.38-0.43 cm 3 / g, pore size 9.0-9.3 nm, particle size 300-950 nm.

2. A nano-sized carbonyl sulfide hydrolysis catalyst, based on the nano-sized carbonyl sulfide hydrolysis catalyst carrier according to claim 1, characterized in that: The composition by weight is: 75-85 parts of γ-Al2O3 powder, 2-5 parts of carboxymethyl cellulose, 2-8 parts of polyvinyl alcohol, 2-10 parts of ammonium bicarbonate, 2-10 parts of citric acid, and 2-12 parts of potassium carbonate.

3. A method for preparing a nano-sized carbonyl sulfide hydrolysis catalyst, based on the nano-sized carbonyl sulfide hydrolysis catalyst according to claim 2, characterized in that: The method steps are as follows: S1, ball milling, separation, and drying: commercially available γ-Al2O3 is nano-sized by ball milling, using zirconium oxide beads as the grinding medium. After the ball milling is completed, the zirconium oxide beads are separated and the sample is centrifuged, the supernatant is discarded, the precipitate is collected, and the precipitate is placed in an oven for drying; S2, primary calcination: calcining the sample prepared in step S1 at high temperature to remove organic matter and crystal water to obtain high-purity nano γ-Al2O3 powder; S3, mixing, granulating, and drying: mixing the γ-Al2O3 powder after the primary calcination with carboxymethyl cellulose, polyvinyl alcohol, ammonium bicarbonate, and citric acid in a certain proportion, granulating the mixture with a disc granulator, and drying the obtained particles; S4, secondary calcination: drying the granules obtained in step S3 and then calcining them again to remove the pore-enlarging agent and leave the mesopores to further increase the specific surface area, thereby obtaining a nano-sized mesoporous blank catalyst carrier; S5, loading active substances: loading the nano-sized mesoporous blank catalyst carrier prepared in S4 with active substance potassium carbonate by immersing the carrier in a solution, and then drying the carrier to obtain a nano-sized catalyst.

4. The method for preparing the nano-carbonyl sulfide hydrolysis catalyst according to claim 3, characterized in that: In step S1, the grinding medium uses 0.1-0.3 mm zirconia beads, the weight ratio of zirconia beads to material is 5:1-7:1, the ball milling speed is 200-700 r / min, the ball milling time is set to 1-6 h, the sample centrifugal speed is 1000-5000 rpm, the centrifugal time is 3-15 min, the drying temperature is 50-100° C., and the drying time is 6-48 h.

5. The method for preparing the nano carbonyl sulfide hydrolysis catalyst according to claim 3, characterized in that: The high temperature calcination in step S2 is performed at a temperature of 400-650° C., a calcination time of 2-6 hours, and a heating rate of 1-8° C. / min.

6. The method for preparing the nano-carbonyl sulfide hydrolysis catalyst according to claim 3, characterized in that: In step S3, the γ-Al2O3 powder calcined in S2 is mixed and granulated with carboxymethyl cellulose, polyvinyl alcohol, ammonium bicarbonate and citric acid in the following weight proportions: 75-85 parts, carboxymethyl cellulose 2-5 parts, polyvinyl alcohol 2-8 parts, ammonium bicarbonate 2-10 parts, and citric acid 2-10 parts.

7. The method for preparing the nano-carbonyl sulfide hydrolysis catalyst according to claim 3, characterized in that: The granulation in step S3 is carried out by a granulator with a granulation speed of 30-80 rpm, a granulation drying temperature of 50-100° C., and a drying time of 6-48 h.

8. The method for preparing the nano-carbonyl sulfide hydrolysis catalyst according to claim 3, characterized in that: The secondary calcination in step S4 is carried out at a temperature of 400-650° C., a calcination time of 2-6 hours, and a heating rate of 1-8° C. / min.

9. The method for preparing a nano-carbonyl sulfide hydrolysis catalyst according to claim 3, characterized in that: The solution loaded with active substances in step S5 is a potassium carbonate solution, which comprises 2-12 parts of potassium carbonate and 82-98 parts of water by weight, and the soaking time is 2-48 hours. The catalyst pellets loaded with active substances are then dried at a temperature of 50-100° C. for 6-48 hours.

10. The method for preparing a nano-carbonyl sulfide hydrolysis catalyst according to claim 3, characterized in that: The average particle size of the γ-Al2O3 powder processed in steps S1 and S2 is 904 nm.

Citation Information

Patent Citations

  • Intermediate temperate carbonyl sulfur hydrolyst and method of preparing the same and use thereof

    CN101108339A

  • Production technology of catalyst for producing hydrogen by reforming methanol vapour at high temperature and application of catalyst

    CN105233815A

  • Carbonyl sulfide hydrolysis catalyst and preparation method thereof

    CN113441124A

  • Carbonyl sulfide hydrolysis catalyst as well as preparation method and application thereof

    CN115869933A

  • Catalyst regeneration method for cos conversion catalyst

    JP2015080767A